2019
DOI: 10.1002/clc.23184
|View full text |Cite
|
Sign up to set email alerts
|

Successful defibrillation verification in subcutaneous implantable cardioverter‐defibrillator recipients by low‐energy shocks

Abstract: Background The subcutaneous implantable cardioverter‐defibrillator (S‐ICD) is an effective alternative to the transvenous one. Defibrillation efficacy depends on maximum device output and on the optimal device location at device implantation. Hypothesis We sought to investigate the defibrillation safety margin in real life clinical practice. Methods We sought to understand what is the efficacy of induced ventricular fibrillation (VF) terminat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 18 publications
1
15
0
Order By: Relevance
“…In addition, the two‐incision inter‐muscular technique results in a more cranial and posterior location of the generator, with better positioning of the coil and generator directly over the fascia without underlying fat, as demonstrated by lower values of shock impedance . Since S‐ICD shock efficacy is associated with system position and impedance, the optimal system position achieved with the inter‐muscular technique may finally result in higher safety margins for ventricular defibrillation . In our series, all patients tested were cardioverted with 65 J.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In addition, the two‐incision inter‐muscular technique results in a more cranial and posterior location of the generator, with better positioning of the coil and generator directly over the fascia without underlying fat, as demonstrated by lower values of shock impedance . Since S‐ICD shock efficacy is associated with system position and impedance, the optimal system position achieved with the inter‐muscular technique may finally result in higher safety margins for ventricular defibrillation . In our series, all patients tested were cardioverted with 65 J.…”
Section: Discussionmentioning
confidence: 90%
“…This technique, in association with the inter‐muscular positioning of the generator, is now the most frequently adopted implantation approach in Europe . These improvements in the implantation technique could yield a further reduction in complication rates and a greater safety margin for arrhythmia cardioversion/defibrillation . Recently, ultrasound‐guided serratus anterior plane block (SAPB), a suitable approach for perioperative analgesia in a number of thoracic surgical procedures, has been proposed to provide anesthesia/analgesia during S‐ICD implantation performed by means of the two‐incision inter‐muscular technique …”
Section: Introductionmentioning
confidence: 99%
“…Compared to a true subcutaneous implantation, the “intermuscular” approach shows better cosmetic results and less device pocket complications and seems to improve DFT testing 36,37 . The interfascial plane between M. serratus anterior and M. latissimus dorsi offers a natural pocket for the device, allowing an atraumatic blunt dissection.…”
Section: Implantation Issues Of Ntv‐icdmentioning
confidence: 99%
“…As pulse generator size is still an issue in children, adolescents, or patients with low body mass index, the development of smaller device cans is expected in future. As mentioned above, an intermuscular device implantation already enabled efficient shocks using lower energies in the DFT testing 37 . Finally, one future concept is to pair a leadless pacemaker in VVI mode with the S‐ICD from the second generation, in order to provide ATP and (post‐shock) bradycardia pacing for patients who are expected to benefit or have a respective indication.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…When implanting physicians alter their implanting technique with these aspects in mind, step-down testing showed a lower average defibrillation threshold [ 18 ]. When implanted intermuscularly with subsequently no fat tissue underneath the generator, another study demonstrated a successful DFT at ≤40J in 94% of the patients [ 19 ]. Impedance The current flow is determined not only by the selected shock output, but also by the resistance of the human body.…”
Section: Comprehension Of Defibrillation Successmentioning
confidence: 99%